2009
DOI: 10.1103/physrevb.79.014422
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility and magnetization fluctuation measurements of mixed gadolinium-yttrium iron garnets

Abstract: We study the magnetic properties of gadolinium-yttrium iron garnet ͑Gd x Y 3−x Fe 5 O 12 , x =3,1.8͒ ferrite ceramics. The complex initial permeability is measured in the temperature range of 2-295 K at frequency of 1 kHz and in the frequency range of 100 Hz-200 MHz at temperatures of 4, 77, and 295 K. The magnetic viscosity-induced imaginary part of the permeability is observed at low frequencies. Measurements of the magnetization noise are made at 4 K. Using the fluctuation-dissipation theorem, we find that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The physical mechanisms leading to dissipation in the form of Gilbert damping are the same ones through which S interacts with the lattice and the transverse spin components are averaged [50][51][52]. According to the FDT, in the lowfrequency limit ω ≪ k B T , the spectral density of transverse spin fluctuations at frequency ω is given by…”
mentioning
confidence: 99%
“…The physical mechanisms leading to dissipation in the form of Gilbert damping are the same ones through which S interacts with the lattice and the transverse spin components are averaged [50][51][52]. According to the FDT, in the lowfrequency limit ω ≪ k B T , the spectral density of transverse spin fluctuations at frequency ω is given by…”
mentioning
confidence: 99%
“…From Fig. 7b, the EDS analysis confirms the empirical formulation to be GdY 2 Fe 5 O 12 , which suggests that the magnetic sample under test is a mixed yttrium gadolinium iron garnet [20][21][22] Gd x Y (3−x) Fe 5 O 12 with x = 1. The sensor was fabricated with the dimensions described in "Design of proposed double-layer sensor" section on a Taconic RF 35 substrate using an LPKF Protomat E33 milling machine.…”
Section: Sample Characterization and Sensor Fabricationmentioning
confidence: 53%
“…The presence of excessive magnetization noise in the magnetic material under study can degrade magnetic field sensitivity and weaken the achievable EDM limit [5,11]. The setup described above was used to look for magnetization noise in Eu 0.5 Ba 0.5 TiO 3 at 4.2 K, but it was found that this noise is at or below the SQUID sensitivity.…”
Section: E Magnetic Susceptibility and Magnetization Noisementioning
confidence: 99%